A Novel Blade‐Jet Coating Method for Achieving Ultrathin, Uniform Film toward All‐Solution‐Processed Large‐Area Organic Light‐Emitting Diodes. Issue 3 (6th May 2016) - Seok, Jae Young; Yang, Minyang
Abstract : This paper reports a new type of large‐area solution coating method that combines a blade coating process and an air‐jet finishing process, and its application to soluble organic light‐emitting diodes (OLEDs) fabrication. The blade coating with stable coating conditions results in a relatively thick uniform wet film. Air‐jet finishing subsequently adjusts the wet film to the target thickness by precisely controlling the flow of the coating solution. By hybridizing the blade coating method and air‐jet finishing technique, functional thin‐film layers can be produced with outstanding quality in terms of thickness uniformity and controllability with high reproducibility. In particular, the blade–jet coating method enables the fabrication of an ultrathin electron injection layer (EIL) of Cs2 CO3 at less than a few nanometer scale over a large area by a solution process. The superior performance of the blade–jet coating method enables solution‐processed large‐area OLED fabrication on both rigid and flexible substrates, with outstanding light‐emitting uniformity. Furthermore, by controlling the thickness and interfacial properties of the EIL, device performance can be optimized. The luminous power efficiency of the optimum OLED device is 8.42 lm W −1, and the luminous nonuniformity is only 2.68% at 6 V over a large area. Abstract : A new type of solution processing method is developed for fabricating large‐area organic light‐emitting diodes with outstanding quality. Blade coating and jet finishing are hybridized as an integrated coating method. Especially, it is the first attempt at applying jet finishing technique to fabricating printed electronic devices, and it shows outstanding performance compared to conventionally fabricated devices.